The Contribution of Islamic Education in Shaping the Social Awareness of the Digital Literate Community: Kontribusi Pendidikan Islam dalam Membentuk Kepedulian Sosial Masyarakat Literasi Digital - Aldi, Muhammad (Faiyadhah | Journal of Islamic Education Management, 2025)
The development of information technology has given birth to a digital literate community that is active in virtual spaces, but it is not uncommon to experience degradation of social awareness due to the flow of unfiltered information. This research aims to reveal the contribution of Islamic education in shaping and improving the social awareness of the digital literate community. This research uses a descriptive qualitative approach with data collection techniques through observation, interviews, and documentation of digital literate community members involved in digital platform-based Islamic education activities. The results show that digital based Islamic education has a significant impact on increasing social values such as tolerance, ethics in interacting online, and concern for social issues. Platforms such as YouTube, Instagram, and podcasts have proven effective in delivering Islamic content that has an impact on changes in community behavior, including increased tolerance, reduced spread of negative content, and active participation in online and offline social activities. Thus, Islamic education has an important contribution in building sustainable social awareness in the midst of a digital literate community, and is able to become a constructive alternative in facing the social challenges of the digital era.